Acacia senegal vs. Acacia seyal gums – Part 1: Composition and structure of hyperbranched plant exudates. (October 2015) - Lopez-Torrez, Lizeth; Nigen, Michaël; Williams, Pascale; Doco, Thierry; Sanchez, Christian
Abstract: Acacia gum is a natural arabinogalactan-protein type polysaccharide widely used in industrial applications. The two varieties of Acacia gum, A. senegal and A. seyal, are hyperbranched polysaccharides rich in arabinose and galactose (PRAG) mainly formed by chains of 3, 6-linked β-D-Gal p substituted in position 6 by side chains of 3-linked α-L-Ara f . Beyond this common structure, A. senegal presented the highest degree of branching (78.2% vs. 59.2%) with more branched galactopyranoses, shorter arabinosyl side branches, and more rhamnopyranoses in terminal position. Circular dichroism experiments evidenced that both Acacia gums were partially structured into polyproline type II helices but in a lesser extent for A. senegal gum, suggesting its less structured organisation. The fingerprint of both Acacia gums and their spectral differences determined by FTIR spectroscopy were described. Analysis of HPSEC-MALLS data suggested that macromolecules of both Acacia gums adopted an ellipsoid-like conformation in solution. The average molecular weight of A. seyal macromolecules was larger than that of A. senegal ones (8.2 × 10 5  g mol −1 vs. 6.8 × 10 5  g mol −1 ). Nevertheless, A. seyal macromolecules appeared more compact and less viscous (Rg : 17.1 nm; [η]: 16.5 mL g −1 ) than A. senegal ones (Rg : 30.8 nm; [η]: 22.8 mL g −1 ). The most compact structure of A. seyal gum can be partly explained by the lowest concentration of charged sugars that induces less electrostatic repulsion, and the highest content of long arabinose side chains that may self-organize and interact between them (e.g. hydrogen bonding, steric effect, etc.). For both Acacia gums, the anisotropy of macromolecules increased with the molecular weight, however, A. senegal macromolecules were the most anisotropic ones. Graphical abstract: Highlights: The two Acacia gums, A. senegal and A. seyal, were described and compared. Both Acacia gums had hyperbranched architectures and ellipsoid-like conformations. Differences in their chemical structure and branching organisation were revealed. A. seyal macromolecules were more compact and less viscous than A. senegal ones. A. senegal macromolecules were more anisotropic than A. seyal ones.